2022
DOI: 10.1002/ccd.30532
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulant versus antiplatelet therapy following transcatheter aortic valve replacement in patients without prior or concurrent indication for anticoagulation: A meta‐analysis of randomized studies

Abstract: Introduction:The antithrombotic management following transcatheter aortic valve replacement (TAVR) in patients who do not have a concurrent indication for longterm anticoagulation therapy is an ongoing source of debate.Methods: We performed a systematic review and meta-analysis to compare direct oral anticoagulants (DOACs) versus antiplatelet therapy after TAVR in patients without a concomitant indication for chronic oral anticoagulation. PubMed, Embase, and Cochrane databases were searched. Only randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Nekoliko radova proučavalo je nastanak SLT-a nakon TAVI zahvata. Zaključeno je da pojava SLT-a nosi tri puta veći rizik od nastanka moždanog udara 27 , a oralni su antikoagulansi najučinkovitiji lijekovi u njezinoj prevenciji [27][28][29] .…”
Section: Uvodunclassified
“…Nekoliko radova proučavalo je nastanak SLT-a nakon TAVI zahvata. Zaključeno je da pojava SLT-a nosi tri puta veći rizik od nastanka moždanog udara 27 , a oralni su antikoagulansi najučinkovitiji lijekovi u njezinoj prevenciji [27][28][29] .…”
Section: Uvodunclassified
“…80 Furthermore, a meta-analysis comparing NOACs with antiplatelet therapy after TAVR in patients without an indication for concurrent OAC found a significantly lower risk of valve thrombosis with nonvitamin K antagonist oral anticoagulant therapy; this coincided with higher allcause mortality. 81 Another meta-analysis of 3 randomized trials comprising 2922 patients without an indication for OAC after TAVR showed that NOACs were associated with a higher risk of all-cause mortality and noncardiac mortality at 15 months, primarily driven by a greater number of major or life-threatening bleeding events. 82 Thus, the preponderance of evidence favors single antiplatelet therapy after TAVR in patients without concurrent indications for OAC.…”
Section: Balancing Prevention Of Leaflet Thrombosis With Risk Of Majo...mentioning
confidence: 99%
“…Thus, OAC use after TAVI had a class III recommendation in the European Guidelines. 2 In this issue of CCI, Moreira et al 4 provide a systematic review and meta-analysis comparing DOACs versus antiplatelet therapy after TAVR in patients without previous indication for OAC. All three precited RCTs were included with a total of 2922 patients, of whom 1463 (50.1%) received DOACs.…”
mentioning
confidence: 99%